2006
DOI: 10.1080/17402520600578731
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Complementarity in the Origins of Autoimmunity: A General Theory Illustrated With a Case Study of Idiopathic Thrombocytopenia Purpura

Abstract: We describe a novel, testable theory of autoimmunity, outline novel predictions made by the theory, and illustrate its application to unravelling the possible causes of idiopathic thrombocytopenia purpura (ITP). Pairs of stereochemically complementary antigens induce complementary immune responses (antibody or T-cell) that create loss of regulation and civil war within the immune system itself. Antibodies attack antibodies creating circulating immune complexes; T-cells attack T-cells creating perivascular cuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…4 Yet another investigator posited a variation on these themes by defining a complementary pair as two proteins capable of stereospecific binding, with the stipulation that they induce molecularly complementary antibodies or T cell antigen receptors. 23 We found that rabbits immunized with human PR3 develop antibodies not only to PR3 but also to human plasminogen, and the converse is also true that mice, chickens, and rabbits inoculated with a complementary-PR3 peptide develop antibodies to this peptide as well as PR3. The most logical explanation for this is that the idiotypic network is responsible for the derivation of the secondary antibody response.…”
Section: Discussionmentioning
confidence: 70%
“…4 Yet another investigator posited a variation on these themes by defining a complementary pair as two proteins capable of stereospecific binding, with the stipulation that they induce molecularly complementary antibodies or T cell antigen receptors. 23 We found that rabbits immunized with human PR3 develop antibodies not only to PR3 but also to human plasminogen, and the converse is also true that mice, chickens, and rabbits inoculated with a complementary-PR3 peptide develop antibodies to this peptide as well as PR3. The most logical explanation for this is that the idiotypic network is responsible for the derivation of the secondary antibody response.…”
Section: Discussionmentioning
confidence: 70%
“…I and others (Root-Bernstein, 1991;RootBernstein and Dobbelstein, 2001;Pendergraft et al, 2004Pendergraft et al, , 2005McGuire and Holmes, 2005;Preston et al, 2005;Root-Bernstein and Couturier, 2006;Root-Bernstein, 2007) have suggested that the simultaneous activation of two sets of complementary T-cell clones (or antibodies) by complementary antigens (as might occur in a mixed infection) would trigger each clone to recognize not only its respective antigen but also its complementary T cell, as targets. Such T-cell targeting of other T cells would create an immunological civil war that could lead to the kind of immunological confusion typifying autoimmune diseases (RootBernstein, 1991;Root-Bernstein, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…The question that arises is what triggers the crucial event that pushes individuals into disease when they have had years of health with circulating autoantibodies. One proposal is that incitement of disease requires provoking the immune system with a pair of molecularly complementary antigens, consequently giving rise to a pair of complementary immune responses - an antibody to a ‘self’ antigen and an antibody against the complementary protein counterpart (5,6). …”
Section: Discussionmentioning
confidence: 99%
“…As posited by the ‘molecular recognition’ theory, this pair of proteins possess a natural potential for physically joining due to inherent properties in shape, amino acid sequence, and hydropathy, which confers structurally complementary shapes likened to a key and a keyhole (2–4). These ideas have been supported by others, who propose that disease can be incited by an initial antibody response to an antigen that is ‘complementary’ to the known autoantigen (5,6). …”
Section: Introductionmentioning
confidence: 88%